Kearifan Lokal Budaya â€œNgarotâ€ dalam Usahatani Padi (Oryza Sativa) Gede Wangi (Study Kasus Di Desa Karedok Kecamatan Jatiede Kabupaten Sumedang) - Agi Dahtiar; Dety Sukmawati; Firli Muldan (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Rice is a food source of energy as well as a staple food for most people, although now many people are starting to replace carbohydrates from rice with other staple foods such as potatoes, corn, sago and wheat. The aim of this research is to determine the form of local cultural wisdom